Beyond Pain: Innovative Approaches to Tension-Type Headache Management and Treatment - Wójcik, Jakub; Błaszczak, Ewa; Dydyk, Martyna; Małachowski, Aleksander; Malinowski, Piotr; Kopczyńska, Urszula; Kopczyński, Cezary; Gurdak, Kinga; Dyrek, Martyna; Partyka, Aleksandra (Journal of Education, Health and Sport, 2024)
Introduction: Tension-type headache (TTH) is a common neurological disorder characterized by bilateral head pain and muscle tension, affecting up to 78% of the population. Despite its prevalence, TTH has historically received less attention than migraines. However, recent years have seen increased interest in understanding its pathophysiology and treatment options. This review comprehensively analyzes TTH management, covering non-pharmacological and pharmacological approaches to guide clinical practice and future research effectively. State of Knowledge: TTHs manifest as bilateral, pressing, encircling head pain, profoundly affecting individuals’ quality of life. Recent years have witnessed increased interest in TTH understanding and treatment. Non-pharmacological interventions, including behavioral modifications, exercise, dietary adjustments, sleep hygiene, physical therapy, psychotherapy, and pharmacological treatments like over-the-counter medications, prophylactic drugs, psychedelics, and botulinum toxin A, have shown promise in alleviating symptoms. Conclusion: This review highlights the multifaceted management of TTH. Non-pharmacological interventions, including behavioral modifications and psychotherapy, offer symptom relief. Body awareness therapy, exercise, and psychotherapy benefit TTH symptoms and quality of life. Paracetamol, ibuprofen, and amitriptyline are standard treatments, with emerging options like psychedelics and botulinum toxin A. Personalizing treatment and understanding TTH mechanisms pose challenges. A multidisciplinary approach is essential for enhancing management and outcomes. More research is required to identify optimal treatments and long-term efficacy. Despite challenges, progress in TTH management brings hope for better patient care.